Advantech Consultancy / Muhammad Zuhilmi Zakaria ... [et al.] - Zakaria, Muhammad Zuhilmi; Mohd Yusof, Mohd Riduan; Raja Daud, Raja Yahya; Jusoh, Ahmad Fadli Iruwan (Faculty of Mechanical Engineering, 2004)
Advantech Consultancy subscribes to the belief that to meet the challenges ahead, we must invest heavily in the marketing skills and in communication skills as well as to be familiar with the latest systems deployed by the industry. Our excellent services include selling security products that usually use to protect house especially bungalow house and building.